Formation of graphic competences of first year architecture and art students (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2025)
The modern paradigm of the educational process development for the near future includes a type of education characterized by a significant amount of independent work and active involvement of students of creative specialties in scientific work, starting from the first year, which would be impossible without strong skills of individual graphic competence. The importance of graphic disciplines for the professional training of an architect, artist, and designer is fundamentally important because they expand the individual capabilities of future professionals. In the current conditions of development of the higher education system, graduates are required to have not only knowledge, skills and abilities in the professional field. Personal qualities such as independence, initiative, originality of thinking, sociability, ability to generate ideas, etc. are equally important. In our opinion, one of the current problems of teaching graphic arts disciplines is the reduction in the number of hours for their study, the lack of the necessary material base (computer labs, for example), which is quite relevant now, and so on. Mutually coordinated programs in certain graphic disciplines can play an important role here. The main approaches to the formation of graphic competencies and evaluation criteria of tasks are considered by the author on the example of long-term research in the process of teaching graphic disciplines to first- and second-year students, as well as teaching the discipline “Drawing” in the preparatory courses of the Center for Pre-University Training (CPT) at the Odesa State Academy of Civil Engineering and Architecture (OSACEA). The article is devoted to the study of the problem of forming graphic competencies of first-year students of architectural and artistic specialties as the basis of their professional technical literacy, as well as to the systematization and generalization of certain methodological approaches to teaching. The study used analytical methods of studying the literature on the methodology of teaching graphic disciplines to creative students, expert analysis of individual graphic works of students and students of the CPT, etc. The results of the research were tested in the educational process, which provides for the improvement and development of this topic in the future.
Keywords: graphic competencies; first-year students of architectural and artistic specialties; pre-university graphic training; geometric and projection drawing; evaluation criteria; technical literacy